2011
DOI: 10.1016/j.jcomdis.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Corpus callosum differences associated with persistent stuttering in adults

Abstract: Recent studies have implicated anatomical differences in speech-relevant brain regions of adults who stutter (AWS) compared to normally fluent adults (NFA). The present study focused on the region of the corpus callosum (CC) which is involved in interhemispheric processing between the left and right cerebral hemispheres. Two-dimensional segmentation of area and voxel based morphometry were used to evaluate the corpus callosum. Results revealed that the rostrum and anterior midbody of the CC was larger in AWS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
3
22
1
Order By: Relevance
“…Unlike our previous study that found a larger anterior CC in AWS (Choo et al, 2011), the current study did not detect any statistically significant differences in CC size and WM volume between children with persistent stuttering, children who recovered from stuttering and typically developing children. Reconciling these findings between children and adults is challenging but could involve the protracted and nonlinear growth pattern of the CC.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike our previous study that found a larger anterior CC in AWS (Choo et al, 2011), the current study did not detect any statistically significant differences in CC size and WM volume between children with persistent stuttering, children who recovered from stuttering and typically developing children. Reconciling these findings between children and adults is challenging but could involve the protracted and nonlinear growth pattern of the CC.…”
Section: Discussioncontrasting
confidence: 99%
“…We recently reported that the overall area of the corpus callosum (CC) and anterior portion of the CC was larger in adults who stutter (AWS) compared to normally fluent adults (Choo et al, 2011). Generally, a larger CC is associated with right hemisphere dominance or reduced hemispheric asymmetry for speech (Dorion et al, 2000; Gootjes et al, 2006; O’Kusky et al, 1988), which is consistent with neurological reports of increased right hemisphere activation or a lack of left hemisphere dominance in stuttering (De Nil et al, 2001; Fox et al, 1996; Neumann et al, 2003, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the current study using dichotic listening infer the same findings of this widespread right hemisphere activation for AWS. Furthermore, the recent findings by Choo et al (2011) seem particularly relevant to the present results. These researchers found the overall size of the corpus callosum to be large in AWS compared to AWNS.…”
Section: Undirected Attention Tasksupporting
confidence: 78%
“…areas associated with self-monitoring, comprehension & fluency) were activated in adults who do not stutter (AWNS) but not among AWS. Structural anomalies of the corpus callosum among AWS were recently reported by Choo et al (2011). These researchers found that AWS exhibited a larger overall callosa compared to AWNS, and suggested that this size difference could be linked to atypical brain function.…”
Section: Dichotic Listening and Stutteringmentioning
confidence: 84%
“…Some studies have shown evidence of decreased activity in the left auditory cortex prior to speech-language therapy and normal or improved activity levels immediately after therapy (3) . Other studies have indicated neuroanatomical differences between individuals who stutter and non-stutterers (18,19) . Some other studies have demonstrated decreased auditory cortex activation and hyperactivation of the motor regions (5) .…”
Section: Discussionmentioning
confidence: 96%